Development of a shredder machine for organic waste - Mohd Rashid, Muhammad Zahid (2025)
Malaysia provides a fertile ground for research owing to its diverse cultural practices, dynamic economy, and pressing environmental issues. One notable area of investigation is the Malaysian passion for food and its impact on organic waste production, especially considering the high density of restaurants across the country. The generation of organic waste in Malaysia is influenced by various factors such as environmental context, local waste composition, and cultural and social practices, all of which must be considered. The objective of this project is to design and simulate an organic waste shredder machine that can aid in managing organic waste effectively. By addressing the unique challenges presented by Malaysia's organic waste, this machine aims to provide a sustainable solution to reduce environmental impact and make the organic waste more useful to our environment. The anticipated outcome of designing an automatic organic waste shredder machine using SolidWorks is to produce a comprehensive and functional final design by the end of this semester. This detailed design will incorporate all necessary specifications and considerations, ensuring it meets the requirements for efficient waste management. Once the design is finalized, it will be ready for fabrication in the following semester, marking a significant step toward implementing practical waste management solutions in Malaysia.